(untitled) (Challenges of the Future, 2026)
Research Question (RQ): Globally, the Competency-Based Curriculum (CBC) enhances skills and employability by aligning education with job market needs, which is vital for development. However, studies on Tanzania’s CBC implementation since 2005 have primarily addressed challenges while neglecting its achievements. This oversight creates a knowledge gap that obscures progress in educational transformation and limits a balanced understanding of reform outcomes. The research question is: What are the documented successes of CBC in Tanzania? Purpose: This narrative literature review examines and documents CBC’s achievements in Tanzania, employing systematic searches across ERIC and AJOAL databases. It synthesizes evidence from government documents and 33 academic studies spanning from 2005 to 2025. Method: A narrative review design was utilized, focusing on narrative synthesis and thematic analysis. Results: Through the lenses of Fullan’s Educational Change Theory (2016) and Systems Theory (1968), five interconnected achievement themes emerged: policy framework development, teacher professional development, curriculum innovation, assessment transformation, and resource mobilization. Theoretical analysis indicates that achievements align with both theories, highlighting success from initiation to implementation phases. Evidence shows that Tanzania’s CBC has overcome initial obstacles, leading to significant educational changes, preparing the country for sustainable development and global competitiveness. Organization: This study encourages a comprehensive understanding of CBC’s positive impacts on Tanzania’s education system. Society: Documenting the key achievements of CBC contributes to a more refined perspective on educational reform. Originality: Among the few studies focusing on the achievements of CBC in Tanzania, this review highlights critical successes often overlooked in existing literature. Limitations / further research: This study relied on published literature, which may overlook undocumented grassroots innovations. Focusing solely on successes, may fail to capture the complexities of CBC’s implementation and its challenges effectively. Future research should aim to include qualitative studies that explore grassroots initiatives and gather firsthand accounts from educators and stakeholders, providing a more comprehensive view of the CBC landscape.